Please answer!
This is substitution btw.
Attachments:
![](https://hi-static.z-dn.net/files/d2c/dc623c2c1e2d4ce7cb137a3d1cf49a90.png)
Answers
Answered by
1
Answer:
here's the answer of this question
please mark as brainlist...
Attachments:
![](https://hi-static.z-dn.net/files/d88/0d0864dd6dad081facaf2b086dc2109e.jpg)
Answered by
1
Step-by-step explanation:
so here -y = x (i)
now substituting (i) in (ii)
9x - 7y = -16
9(-y) - 7y = - 16
-9y - 7y = -16
-16y = -16
y = 1
so therefore x = -(1)
x = -1
Similar questions